Análise de propriedades dosimétricas de materiais quanto à dependência energética usando simulação de Monte Carlo - Tobias, Isabella Pereira (2021)
The radiotherapy treatments are mostly carried out through irradiation with photon beams of different energies. For the dosimetric measurements in these beams, the most used techniques are thermoluminescence (TL) and optically stimulated luminescence (OSL). It is necessary to know their dosimetric characteristics such as the variation of their response with the energy of the radiation beam. The aim of this work was to study the energy dependence of the relative response of different materials when irradiated in low to high energy monoenergetic photon beams, 10 keV to 1 MeV. For this purpose, relative response curves as a function of photon energy in water and air were obtained for commercially available materials such as Calcium Sulfate doped with Dysprosium - CaSO4:Dy, Lithium Fluoride - pure LiF and doped with materials such as Mg, Cu , P, and Ti, and aggregated with PTFE; and promising new materials for use in dosimetry as crystals varying the concentration of barium oxide, cadmium oxide, dilanthanum trioxide; and crystals composed of pure BaGd2ZnO5 and doped with Er and Yb. The relationship was studied by Monte Carlo simulation using the code MCNP6.2. The results for widely studied materials were consistent with the experimental results already presented in the literature. For the new materials, it was possible to observe their behavior as a function of the beam energy. However, no material studied approached the interesting linearity presented by LiF.